Cloning, heterologous expression, and expression analysis of SinSyn7 gene from Sinomenium acutum - Jiabei Chen; Xinyu Chen; Li Zhang; Shiyi Huang; Xinbo Chen; Xueshuang Huang; Hua Yang (PLoS ONE, 2025)
The main component of Sinomenium acutum, sinomenine, has anti-inflammatory, analgesic, and immunosuppressive effects. In order to achieve the biosynthesis of sinomenine, the synthase gene SinSyn7 was cloned from Sinomenium acutum and expressed heterologously in brewing yeast WAT11, and its bioinformatics analysis and tissue-specific expression were investigated. The results showed that the coding region (CDS) of SinSyn7 is 1602 bp, encoding 523 amino acids, with an isoelectric point pI of 7.28. The SinSyn7 protein is a hydrophilic protein, without signal peptides, and has a transmembrane domain. It belongs to the cytochrome P450 superfamily and is mainly composed of α-helices and irregular coils to form a secondary structure. The molecular docking results showed that the binding free energies of the six ligands to SinSyn7 ranged from −9.0 to −7.3 kcal· mol-1, and all exhibited strong binding abilities. Alanine scanning and saturation mutagenesis analysis revealed that there are 5 key amino acid residues involved in the SinSyn7 catalyzed (S)-reticuline sophocarpine reaction. The content trends of sinoacutine and sinomenine in different tissues of Sinomenium acutum were consistent. The qRT-PCR results showed that the expression level of the SinSyn7 gene was relatively high in the rhizome of Sinomenium acutum. This study provides insights into further revealing the role of SinSyn7.